Role Reversal: When Activists Are Treated Like Criminals. Conversations on the Criminalization of Environmental Activism in Belgium, France, and the UK - Bocquet, Nicolas; Del Fa, Sophie; Hayes, Graeme; Knops, Louise; Vrydagh, Fanny (Surveillance & Society, 2025)
Recent years have seen a hardening of repressive and surveillance measures against protest and contentious activities in Western societies. Although these measures are not socially neutral and primarily target marginalized populations, they are now increasingly targeting environmental activists and the latest wave of resistance practices that denounce the capitalist contradictions at the heart of liberal democracies. In this piece, we bring together insights and discussions from a roundtable on the criminalization of environmental activism (October 19, 2023, Brussels) as well as empirical insights from the French, UK, and Belgian context where a “role-reversal” between environmental activism and criminality can be observed. Our roundtable text discusses and documents the types of legal, political, and discursive practices that are being deployed by Western states to delegitimize and criminalize environmental contestation—e.g., through state surveillance practices, new legal instruments, court procedures, and the rise of the “eco-terrorist” discourse—while also reflecting on the simultaneity of environmental activism criminalization with a broader authoritarian tendency and increasing legitimation of far-right practices and ideologies.